Long‐term outcomes in patients with normal coronary arteries, nonobstructive, or obstructive coronary artery disease on invasive coronary angiography. Issue 9 (3rd July 2021) - Hanson, Christopher A.; Lu, Edwin; Ghumman, Saad S.; Ouellette, Michelle L.; Löffler, Adrián I.; Beller, George A.; Bourque, Jamieson M.
Abstract: Background: Normal or near normal coronary arteries (NNCA) or nonobstructive coronary artery disease (CAD) are commonly found on invasive coronary angiography (ICA). Hypothesis: We aimed to determine long‐term outcomes by severity of CAD in a contemporary cohort of patients undergoing ICA for evaluation for ischemic heart disease. Methods: We assessed a consecutive cohort of 925 patients who underwent non‐emergent ICA over 24 months. Cardiac death (CD), nonfatal myocardial infarction (NFMI), late revascularization, and medication use were assessed. Results: Follow‐up data was available in 850 patients. Of patients without heart failure, at a median of 6.0 years, there was a significant decrease in survival free from CD or NFMI, and from all cardiac events, for those with obstructive CAD compared with patients with NNCAs or nonobstructive CAD ( p  < .001 for both). No differences between NNCA and nonobstructive CAD patients in rates of CD or NFMI (2.0% vs. 2.1%/year, p  = .58) or all cardiac events (2.4% vs. 2.9%/year, p  = .84) were observed. Conclusion: Long‐term follow‐up in a contemporary cohort of consecutive patients undergoing non‐emergent ICA for detection of CAD showed no difference in annual rates of CD or NFMI, or total cardiac events, in patients with NNCAs versus those with nonobstructive CAD, whereas patients with obstructive CAD had significantly more events. Event rates were low and similar by gender. Use of aspirin, lipid lowering therapy, and beta‐blockers increased in all subgroups after ICA. We speculate this may explain the low incidence of subsequent cardiac events, and similar event rates in patients with NNCA and nonobstructive CAD, even in patients presenting with non‐ST‐elevation MI.